Contemporary conflicts and challenges - Digby, Bob; Warn, Sue (TSG - Top spec geography, 2012)
This book explores the geography behind contemporary conflicts. It investigates geographical aspects of conflict at a variety of scales; from the local (the new HS2 rail link), to the national (including separatism e.g. Chechnya) and the international (Darfur). It also considers some of the challenges posed by multi-cultural societies.